DEVELOPMENT OF LEARNING APPLICATIONS FOR EARLY CHILDREN - Estu Sinduningrum; Muhammad Irfan Faris (Jurnal Teknik Informatika dan Komputer, 2023)
Introducing the Hijaiyah letters to elementary school children is very important at the Al-Qur'an Education Park, elementary school level and Islamic Religious Education in Kindergarten. The problem felt by students at SDN JATIRANGGA II is that they still use media such as blackboards, books and posters in learning hijaiyah letters during Islamic Religious Education subjects. So students have a little difficulty in getting material related to learning hijaiyah letters. To overcome this problem, the author created an Android-based learning application using the multimedia development life cycle (MDLC) method. Making applications specifically for children under 10 years of age. This application only discusses hijaiyah letters and the harakat or punctuation marks in hijaiyah letters. The results of this research can make it easier for teachers and students to learn material related to hijaiyah letters and harakat. Based on the questionnaire that was given to teachers and students, 89.6% agreed that this application could help children understand the letters and hijaiyah characters. So this Android-based learning media can help teaching activities at SDN Jatirangga II.